Production and market performance of dairy goats in Kongwa and Mvomero districts: Value chain option - Mpelangwa, E.M. (Sokoine University of Agriculture, 2013)
This study determined production and market performance, through value chain analysis of dairy goats and its products with gender perspective in Mvomero and Kongwa districts, Tanzania. The specific objectives were: (i)To map key players of dairy goats and its products value chain (ii)To examine market performance of dairy goats and its product (iii)To assess effect of gender on dairy goat profitability and (iv)To examine the production performance of dairy goats. Data were collected from 106 farmers who kept 250 dairy goats, 40 processors/collectors and 60 consumers. Descriptive statistics, gross margin, net margin analysis and Data Envelope Analysis were carried with regard to each specific objective. The study found that the chain is comprised of five key players with three main products. These key players were farmers, input suppliers, grain millers, food vendors and consumers. The main products were fresh milk, manure, and offspring. Based on market structure the dairy goat milk was accepted based on its nutritious value. On market performance about 30% of the farmers had positive gross margin while 20% of farmers were making profit through having positive net margin. Based on gender effect on profitability, there was no sufficient evidence to reject the null hypothesis that there was no profit difference among different genders. For the case of production performance technical efficiency was 0.75 in both output and input orientations. This indicates that farmers were able to reduce 25% of the production cost to produce the same level of milk and manure, or they could increase the output by 25% using the same level of input. On other hand, scale efficient was 0.77 on input orientation. This further indicates that there was still a room to benefit on economic of scale, taking into consideration about 90% of the farmers were operating on increasing return to scale.